Psychological stress factors among university students in Bangladesh during the third wave of the COVID-19 pandemic - Tama, Riffat Ara Zannat; Hoque, Md Mahmudul; Islam, Md Sayemul; Imam, Nazneen; Alam, Mohammad Jahangir; Ethen, Dilshad Zahan; McKenzie, Andrew M. (Frontiers in Education, 2025)
IntroductionThe COVID-19 pandemic has had profound impacts on multiple aspects of human life, including public health, economic stability, and education systems worldwide. During the Omicron variant-led wave, Bangladeshi university students faced significant disruptions, such as delays in graduation and limited opportunities for income-generating activities. This study offers a new attempt to investigate the psychological stress experienced by Bangladeshi university students and the sources of that stress.MethodsA cross-sectional study was conducted using multiple linear regression analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM). Socioeconomic and psychological characteristics were included as independent variables to assess their relationship with psychological stress.ResultsThe findings reveal that relationship issues, scholastic delays, lack of recreation, and poor internet connectivity are significant contributors to psychological stress among university students. Relationship complications emerged as the strongest predictor (β= 0.413, p < 0.001), followed by scholastic delays (β= 0.286, p = 0.010), lack of recreation (β= 0.118, p = 0.032), and poor family harmony (β= 0.114, p = 0.024).DiscussionThis study represents one of the first systematic efforts to examine the psychological stressors of university students in Bangladesh. The results highlight the multidimensional nature of student stress and emphasize the urgent need for targeted interventions from both governmental and non-governmental organizations. The insights also have broader implications for understanding student mental health in other developing countries facing similar socioeconomic and infrastructural constraints.